Harpun, pan mysz i Arnold Mocny – przykłady metafor męskości w felietonach Małgorzaty Domagalik - Majewska, Magdalena (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
<span dir="ltr" style="left: calc(var(–scale-factor)*74.66px); top: calc(var(–scale-factor)*482.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0367);" role="presentation">The paper presents the feminist and the traditional metaphors of masculinity <span dir="ltr" style="left: calc(var(–scale-factor)*393.83px); top: calc(var(–scale-factor)*482.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00241);" role="presentation">using <span dir="ltr" style="left: calc(var(–scale-factor)*75.25px); top: calc(var(–scale-factor)*496.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00488);" role="presentation">examples from Małgorzata <span dir="ltr" style="left: calc(var(–scale-factor)*186.54px); top: calc(var(–scale-factor)*496.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.963108);" role="presentation">Domagalik’s <span dir="ltr" style="left: calc(var(–scale-factor)*238.78px); top: calc(var(–scale-factor)*496.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01217);" role="presentation">subjective texts. The columnist shows three <span dir="ltr" style="left: calc(var(–scale-factor)*75.21px); top: calc(var(–scale-factor)*510.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.998113);" role="presentation">types of male personalities: <span dir="ltr" style="left: calc(var(–scale-factor)*187.19px); top: calc(var(–scale-factor)*510.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.05235);" role="presentation">Harpun (<span dir="ltr" style="left: calc(var(–scale-factor)*224.83px); top: calc(var(–scale-factor)*510.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01772);" role="presentation">Harpoon<span dir="ltr" style="left: calc(var(–scale-factor)*260.44px); top: calc(var(–scale-factor)*510.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.99657);" role="presentation">), <span dir="ltr" style="left: calc(var(–scale-factor)*268.73px); top: calc(var(–scale-factor)*510.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.981209);" role="presentation">pan mysz (<span dir="ltr" style="left: calc(var(–scale-factor)*312.14px); top: calc(var(–scale-factor)*510.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.971554);" role="presentation">mister mouse<span dir="ltr" style="left: calc(var(–scale-factor)*364.23px); top: calc(var(–scale-factor)*510.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0481);" role="presentation">) and <span dir="ltr" style="left: calc(var(–scale-factor)*387.96px); top: calc(var(–scale-factor)*510.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.968585);" role="presentation">Arnold <span dir="ltr" style="left: calc(var(–scale-factor)*74.69px); top: calc(var(–scale-factor)*524.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.925206);" role="presentation">Mocny (<span dir="ltr" style="left: calc(var(–scale-factor)*106.22px); top: calc(var(–scale-factor)*524.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.93198);" role="presentation">Arnold the Strong<span dir="ltr" style="left: calc(var(–scale-factor)*173.52px); top: calc(var(–scale-factor)*524.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.95521);" role="presentation">). <span dir="ltr" style="left: calc(var(–scale-factor)*180.87px); top: calc(var(–scale-factor)*524.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00133);" role="presentation">Harpoon <span dir="ltr" style="left: calc(var(–scale-factor)*217.68px); top: calc(var(–scale-factor)*524.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.906547);" role="presentation">is a <span dir="ltr" style="left: calc(var(–scale-factor)*231.80px); top: calc(var(–scale-factor)*524.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.992126);" role="presentation">weapon <span dir="ltr" style="left: calc(var(–scale-factor)*264.43px); top: calc(var(–scale-factor)*524.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.958582);" role="presentation">in the fight against stereotypes whereas <span dir="ltr" style="left: calc(var(–scale-factor)*75.08px); top: calc(var(–scale-factor)*538.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.954533);" role="presentation">mister mouse <span dir="ltr" style="left: calc(var(–scale-factor)*128.06px); top: calc(var(–scale-factor)*538.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.971487);" role="presentation">is man out of his depth, who doesn’t show any traditional masculine traits. <span dir="ltr" style="left: calc(var(–scale-factor)*74.91px); top: calc(var(–scale-factor)*552.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01604);" role="presentation">On the other side <span dir="ltr" style="left: calc(var(–scale-factor)*146.88px); top: calc(var(–scale-factor)*552.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.960246);" role="presentation">Arnold the Strong <span dir="ltr" style="left: calc(var(–scale-factor)*218.51px); top: calc(var(–scale-factor)*552.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.955915);" role="presentation">is a <span dir="ltr" style="left: calc(var(–scale-factor)*233.80px); top: calc(var(–scale-factor)*552.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00398);" role="presentation">personification <span dir="ltr" style="left: calc(var(–scale-factor)*296.31px); top: calc(var(–scale-factor)*552.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0038);" role="presentation">of male strength. The method<span dir="ltr" style="left: calc(var(–scale-factor)*75.25px); top: calc(var(–scale-factor)*566.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.995371);" role="presentation">ological structure is based on a <span dir="ltr" style="left: calc(var(–scale-factor)*200.29px); top: calc(var(–scale-factor)*566.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.997489);" role="presentation">linguistic and cultural analysis of metaphors shown in <span dir="ltr" style="left: calc(var(–scale-factor)*74.94px); top: calc(var(–scale-factor)*580.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.99383);" role="presentation">Małgorzata <span dir="ltr" style="left: calc(var(–scale-factor)*122.47px); top: calc(var(–scale-factor)*580.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.962434);" role="presentation">Domagalik’s <span dir="ltr" style="left: calc(var(–scale-factor)*173.93px); top: calc(var(–scale-factor)*580.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.99945);" role="presentation">columns.